The Role of Maxims in The Process of Investigations: A Case Study in Situbondo Resort Police Office - Yopi Thahara; Ahmad Yusuf Firdaus; Firqo Amelia (JURNAL ARBITRER, 2018)
This study aims to reveal the role of maxim in the conversation between the investigators and suspects in giving information during the making of investigation reports in Situbondo police office. This is an interdisciplinary linguistic research that utilizes linguistic and pragmatic disciplines. The theory used to analyze the data in this study is the theory of speech acts initiated by Searle. This is a qualitative descriptive research, and it produces deep descriptions of the words, writings, and behaviors that can be observed from a specific individual, group, society, or organization in a particular context that is holistically studied. The result of this research is the role of maxim in the process of investigation and the degree of the trustworthiness.